2021
DOI: 10.1108/pm-05-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Current situation, challenges and future development directions of facilities management in Kosovo

Abstract: Purpose While facilities management (FM) in Kosovo is a constantly growing discipline, the studies so far in Kosovo have been scarce and too general. The purpose of the paper is to discuss the current situation of FM in Kosovo, identify challenges and recommend new future development directions of the sector with regard to capabilities of facility managers, integration of technology in FM and FM standardization.Design/methodology/approach The present study uses qualitative method by using semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Inadequate and ineffective funding management was identified as the root cause of other FM problems. Similar findings in other studies (Hoxha et al, 2022;Mazele and Amoah, 2022) indicated that a lack of budget was the most significant issue for both public and private buildings. Other problems included lack of FM human resources and supplies and ineffective FM strategies, which focus on building sustainability and key performance indicator (KPI) problems.…”
Section: Problems In Fmsupporting
confidence: 90%
“…Inadequate and ineffective funding management was identified as the root cause of other FM problems. Similar findings in other studies (Hoxha et al, 2022;Mazele and Amoah, 2022) indicated that a lack of budget was the most significant issue for both public and private buildings. Other problems included lack of FM human resources and supplies and ineffective FM strategies, which focus on building sustainability and key performance indicator (KPI) problems.…”
Section: Problems In Fmsupporting
confidence: 90%
“…It has a significant impact on building operations and end-user work performance. Hoxha et al (2021) argue that the building industry and FM professional has not yet realized the importance of adopting IoT technologies in their building as they create the complex configuration of the connection between physical asset of IoT and dynamic maintenance networks. Johannes et al (2021) found fifteen barriers and seventeen smart-maintenance drivers and created the maturity dimensions.…”
Section: Iot's Impact On Facilities Managementmentioning
confidence: 99%
“…Facility managers must be knowledgeable in a wide range of management and leadership skills. Furthermore, to be effective, FMs must have both operational and management skills (Hoxha et al, 2021),…”
Section: The Concept Facility Management (Fm)mentioning
confidence: 99%